Analysis of South African listed real estate to serve as an inflation hedge versus other asset classes - Erasmus, Warren (Department of Finance and Tax, 2016)
Purpose - The analysis of the South Africa property sector to provide an effective inflation hedge has not been researched to the same extent as other more developed countries. In addition, the South African property sector has been excluded from international studies owing to its underdevelopment and inconsistent legislative environment. However, post 2013 the new SA REIT legislation was promulgated putting it on par with its international counterparts. In addition from 2012-2013 the market capitalisation of the sector doubled. The study reviews inflation's relationship with direct and indirect property, and the study compares this relationship to other asset classes available to investors. It further reviews the difference between inflation hedging versus inflation protection, using different measures of inflation hedging and also reviews the various component parts of inflation being expected versus unexpected inflation. Design/methodology/approach - The methodology in this study is adopted from the extensive research previously applied to other more developed markets. Additionally, technical and fundamental analysis of returns, correlations, risks and returns were applied.